Solid Waste Management in Small Municipalities: When and How to Discuss a New Fee? - Merloto, Murilo Cesar; Mancini, Sandro Donnini; Candiani, Giovano; Medeiros, Gerson Araujo de; Paes, Michel Xocaira; Viana, Ednilson; Souza, Ricardo Gabbay de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2024)
Solid waste management (SWM) at the municipal level is challenging for developing countries. Typically, the service runs at an economic loss and is of low quality, with high environmental impacts. The research aimed to evaluate how budgetary and public policies may affect the quality of solid waste management in small municipalities from underdeveloped countries. This study reports the economic impact of the operational routine, legislation, taxes, and total SWM costs in a small municipality of Brazil (36,000 inhabitants). Eleven types of waste and related services were evaluated from 2017 to 2020. Results show that the SWM budget would have to increase from the current 3.64% of the annual city budget to 7.48% to supply this management's financial needs under a future scenario of full legislative compliance. The costs required for this compliance would increase expenses from US$ 29.09 to US$ 46.05 per inhabitant per year. Alternatives to solve or alleviate the problem are efficiency's continuous improvement, new types of fundraising, inter-municipal cooperation, and increased inspection, especially related to establishing the legal responsibilities for waste generators. A new fee could also be discussed since this municipality (as well as more than half of Brazilian cities) has no specific charge for SWM. A US$ 9.40 per inhabitant/year charge would cover the operational costs related to domestic solid waste.